Implementation Of The Pattern Guessing Game (Letters) In Introducing Letters To Children Aged 5-6 Years At Kejora Paud In The 2025 Academic Year - Susianti, Emi; Marzoan, Lalu; Eliyana, Eliyana (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to describe the implementation of guessing game patterns (letters) in introducing letters to children aged 5-6 years at PAUD Kejora. This research was conducted at PAUD Kejora group B with 10 students.This type of research is qualitative research with a case study approach, the data collection techniques used in this research are observation, interviews, and documentation. Information collected comes from accompanying teachers, principals and students. The data analysis technique used in this research is through several stages including 1) Data condensation. 2) Data Presentation, and 3) Drawing Conclusions.The results of this study describe the results of the implementation of the Guess the Pattern (Letters) Game proved effective as a method of letter recognition for children aged 5-6 years. This game-based approach successfully fulfills the ideal learning principles, including active participation (BSH), immediate feedback, and high intrinsic motivation. The combination of game-based learning, outbound, interactive lectures and Q&A created a multisensory learning experience, improving letter memory retention (MB) and fine motor skills (BSH). Although there were challenges, such as difficulty distinguishing similar letters (MB) and technology dependency (MB), the differentiation approach and outdoor learning successfully mitigated their impact.Key enabling factors, such as: multisensory stimulation, high engagement (BSH), and group collaboration (BSB), play an important role in creating a holistic learning ecosystem. However, cognitive, motor and emotional regulation challenges require more systematic strategies, such as strengthening sensomotor activities and intensive mentoring. Overall, the implementation of this game shows that a game-based approach in an outdoor setting is able to optimize children's cognitive, motor and socio-emotional development, although it requires adjustments to overcome the obstacles that arise.